The polarity asymmetry of negative strengthening: dissociating adjectival polarity from face- threatening potential - Mazzarella, Diana (My University, 2021)
The interpretation of negated antonyms is characterised by a polarity asymmetry: the negation of a positive polarity antonym (X is not interesting) is more likely to be strengthened to convey its opposite (‘X is uninteresting’) than the negation of a negative polarity antonym (X is not uninteresting to convey that ‘X is interesting’) is. A classical explanation of this asymmetry relies on face management. Since the predication of a negative polarity antonym (X is uninteresting) is potentially face-threatening in most contexts, the negation of the corresponding positive polarity antonym (X is not interesting) is more likely to be interpreted as an indirect strategy to minimise face-threat while getting the message across. We present two experimental studies in which we test the predictions of this explanation. In contrast with it, our results show that adjectival polarity, but not face-threatening potential, appears to be responsible for the asymmetric interpretation of negated antonyms.
Keywords: negation; polarity; antonyms; negative strengthening; politeness; face